The quantitative changes trend of Iranian schools building from the early Islamic centuries until Qajar Era - Kaki, A.; Mohammad Moradi, A.; Memarian, G.H. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Like any other piece of art indicating signs of past originalities, the Iranian architectural works are required to be recognized and introduced. From amongst the architectural subjects, schools have the most links in the most elegant formats with the past heritage, nature and environment and enjoy a certain importance. The important point concerning studying Iranian schools architecture is to recognize the trend of architecture continuance of these buildings, especially during Islamic era. From amongst the important factor in studying the continuity in schools architecture include quantitative continuity and number of schools built during each era, which shall be an effective guide in recognition of the indicated values. Based on such type of analytical vision, studying quantitative continuity of building schools and number of the same during different post-Islamic eras until Qajar Era in Iran is the main context and purpose of this study. The generality of the study represents an analysis on the number and quantitative continuance of building schools during different eras of Iran Islamic architecture, beyond which, the quantitative trend of building and important cities in terms of number of built schools in each era are identified. This study is of historical- interpretation type and collection the data and conclusion are based on comparative studies conducted on different library and field resources and refining and choosing the most correct and reliable statistics from amongst the available information. In Conclusion, the number of schools in all the post-Islamic eras in Iran, the most important cities and eras in terms of quantity of building schools are determined and relationship between political importance of cities and number of built schools in them is observed. According to the aforementioned interpretations, this study shall clarify a documented role to plan in order to take benefit from the available information in an optimized manner.